2022
DOI: 10.3389/fpsyt.2022.992256
|View full text |Cite
|
Sign up to set email alerts
|

Results from PSIPROSPER: A multicenter retrospective study to analyze the impact of treatment with paliperidone palmitate 1-month on clinical outcomes and hospital resource utilization in adult patients with schizophrenia in Portugal

Abstract: BackgroundSchizophrenia is a chronic psychiatric disorder with a significant impact worldwide. The early onset and its relapsing nature pose a significant challenge to patients and caregivers. The PSIPROSPER study aimed to characterize the real-world context of schizophrenia treatment in Portugal and to measure the impact of including paliperidone palmitate 1-month formulation (PP1M) in the clinical outcomes (relapses and hospitalizations) and healthcare resource utilization, in a context in which payment sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
1
0
0
Order By: Relevance
“…In the same study, during the period of 18 months, 72.1% patients with schizophrenia treated with oncemonthly injectable paliperidone palmitate did not have hospitalization. Another study 17 , conducted on smaller sample (n=51) which evaluated hospitalization rates of patients with schizophrenia treated with once-monthly paliperidone palmitate showed that in the period of 12 months only 9.8% patients had psychiatric hospitalization which is in line with our results. The same study showed that 74% patients during the period of 12 months, besides once-monthly injectable paliperidone palmitate, had additional oral antipsychotic therapy which is considerably higher than our results of 30.9%.…”
Section: Discussionsupporting
confidence: 91%
“…In the same study, during the period of 18 months, 72.1% patients with schizophrenia treated with oncemonthly injectable paliperidone palmitate did not have hospitalization. Another study 17 , conducted on smaller sample (n=51) which evaluated hospitalization rates of patients with schizophrenia treated with once-monthly paliperidone palmitate showed that in the period of 12 months only 9.8% patients had psychiatric hospitalization which is in line with our results. The same study showed that 74% patients during the period of 12 months, besides once-monthly injectable paliperidone palmitate, had additional oral antipsychotic therapy which is considerably higher than our results of 30.9%.…”
Section: Discussionsupporting
confidence: 91%